Australian banking - Gifford, J. K. ([St. Lucia, Brisbane] : University of Queensland Press, 1967)
The position of the banks in the money and capital markets and the role of monetary policy .
First ed. by J. K. Gifford and J. Vivian Wood.
Includes index
Includes bibliographical footnotes.
ii 15/01/2019
Loans
Keywords: Banks and banking; Money; Bank management; Banking law; Economic policy